Pour réussir le bilinguisme judiciaire au Nouveau-Brunswick - Bastarache, Michel (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1983)
This article outlines the different attempts over the years to secure the status of the French language in legal proceedings in New Brunswick. A 1968 opinion reiterated rulings dating from 1650 and 1784 that English is the applicable language in all proceedings at the provincial level. Subsequent rulings have modified the state of events but in most cases on paper only. In 1980, the New Brunswick Association of Lawyers set up an investigative commitee whose tasks were to identify any inherent problems in the use of French in provincial courts and to find a way of integrating the two official languages into New Brunswick's legal practice with as little animosity as possible. The publication of the committee's report led to new legislative measures assuring the implantation of bilingualism in its provincial courts. Although legislators had hoped for speedier implementation of the measures, it is important to keep in mind the difficult context in which these changes are taking place. A change in attitude is apparently necessary before the transformation is complete.